A Water‐Proof Triboelectric–Electromagnetic Hybrid Generator for Energy Harvesting in Harsh Environments. Issue 6 (23rd December 2015) - Guo, Hengyu; Wen, Zhen; Zi, Yunlong; Yeh, Min‐Hsin; Wang, Jie; Zhu, Liping; Hu, Chenguo; Wang, Zhong Lin
Abstract : Packaging is a critical aspect of triboelectric nanogenerators (TENG) toward practical applications, since the performance of TENG is greatly affected by environmental conditions such as humidity. A waterproof triboelectric–electromagnetic hybrid generator (WPHG) for harvesting mechanical energy in harsh environments is reported. Since the mechanical transmission from the external mechanical source to the TENG is through a noncontact force between the paired magnets, a fully isolated packaging of TENG part can be easily achieved. At the same time, combining with metal coils, these magnets can be fabricated to be electromagnetic generators (EMG). The characteristics and advantages of outputs from both TENG and EMG are systematically studied and compared to each other. By using transformers and full‐wave rectifiers, 2.3 mA for total short‐circuit current and 5 V for open‐circuit voltage are obtained for WPHG under a rotation speed of 1600 rpm, and it can charge a supercapacitor (20 mF) to 1 V in 22s. Finally, the WPHG is demonstrated to harvest wind energy in the rainy condition and water‐flow energy under water. The reported WPHG renders an effective and sustainable technology for ambient mechanical energy harvesting in harsh environments. Solid progress in both the packaging of TENG and the practical applications of the hybrid generator toward practical power source and self‐powered systems is presented. Abstract : A waterproof triboelectric–electromagnetic hybrid generator, which consists of a triboelectric nanogenerator (TENG) and an electromagnetic generator, is demonstrated for harvesting mechanical energy in harsh environments. The characteristics of the outputs from both generators in the hybrid mode are systematically studied. Solid progress in both TENG packaging and the applications of the hybrid generator is presented.